Exploring the Factors Associated with Discharge Before Noon at Universitas Indonesia Hospital in 2024 - Shalawa, Radhica El; Basabih, Masyitoh; Sari, Erna Puspita (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2026)
Only 20% of inpatients at Universitas Indonesia Hospital (RSUI) were discharged before noon (12:00 PM) in 2024, indicating that the hospital has not yet achieved its early discharge target (70%). While early discharge is recognized as a quality indicator, limited evidence exists on the factors influencing discharge timeliness in teaching hospitals. This study aimed to identify factors associated with inpatient discharge before noon at Universitas Indonesia Hospital. A retrospective design was employed using secondary data from the Hospital Information System for the period January-December 2024. Data were analyzed using univariate analysis, bivariate chi-square tests, and multivariate logistic regression. Six variables were significantly associated with discharge timing: discharge planning, treatment type, patient age, financial coverage, length of stay, and discharge day. These findings underscore the importance of strengthening discharge planning, optimizing clinical and administrative workflows, and enhancing interdepartmental coordination. Managerial contributions were also emphasized, particularly the optimization of the Hospital Information System (HIS), inter-unit coordination, and the implementation of strategies such as early physician orders, morning rounds, standardized discharge checklists, effective communication, and staff training. Further research should examine additional factors, including human resource availability and the involvement of medical students, which are unique to teaching hospitals.